Drainage of subconjunctival hemorrhage through conjunctival lymphatic pathways - Ashton Zheng-Boon Lau; Grace YF. Tang; William H. Morgan; Geoffrey ZP. Chan (American Journal of Ophthalmology Case Reports)
Purpose: To demonstrate the role of ocular lymphatic involvement in aiding the drainage and resolution of subconjunctival hemorrhage. Methods: We present the case of a 63-year-old Caucasian female who developed a subconjunctival hemorrhage following the administration of a subconjunctival anesthetic during cataract surgery. Intraoperative optical coherence tomography was utilized to image these structures within the deep and middle conjunctival-Tenon's space. Results: Subconjunctival hemorrhage was visualized and saccular blood-filled structures developed adjacent to sites of hemorrhage. Intraoperative optical coherence tomography confirmed the presence of blood within structures containing partitions reminiscent of valvular leaflets, indicating their lymphatic origin. Rapid resolution of the subconjunctival hemorrhage was noted during the immediate postoperative period. Conclusion: Subconjunctival hemorrhage may have its resolution assisted by conjunctival lymphatic vessels. Our findings confirm that lymphatic structures may play an under-appreciated role in assisting the clearance of macromolecules from the subconjunctival space.